Developing an evidence‐based guideline for the management of exposure to hepatitis B at a Victorian tertiary hospital - Anna B. Pierce; Jude Armishaw; Stacey Aitchison (Elsevier, 2013)
Abstract Objective: To develop a guideline for the management of potential exposures to hepatitis B virus (HBV) at The Alfred Hospital, based on results of clinical audit, database analysis and literature review. Methods: i) Retrospective record review of all histories of patients who received HBV immunoglobulin (HBIG) at The Alfred between 1/1/2007 and 30/9/2011. ii) Analysis of HBV serological results of men who have sex with men (MSM) on Victorian NPEP Service (VNPEPS) database between 10/8/2005 and 31/12/2011. iii) Literature review to determine risks of HBV transmission and best practice for prevention of HBV transmission. Results: A total of 48 patients were potentially exposed to HBV and given HBIG, with sexual exposure the most common indication (n=20). The source was reported to be HBsAg positive in one case only. Of the MSM on the VNPEPS database, 63% were immune to HBV, and only 0.5% of patients tested had evidence of chronic HBV infection. The recommendations for use of HBIG in The Australian Immunisation Guidelines are ambiguous and differ from other international guidelines. Conclusion: This audit at a tertiary referral hospital identified problems with the management of those potentially exposed to HBV. In those non‐immune patients exposed to HBV, the combination of HBIG plus vaccination provides the best protection against infection. The risk of transmission of HBV is highly variable; rates of chronic HBV in PWID and MSM in Australia are low and do not warrant use of HBIG unless the source is known to be HBsAg positive.